Gröna miljöer på skolgården - Ingemansson, Karin (2011)
School ground development is becoming increasingly popular in Sweden today and local community settings are also seen as an important resource for education. The debate today raises the question about the whole city’s pedagogic potential. Outdoor education is a pedagogy that comprises outdoor learning with focus on the sensual experiences. Connection to the classroom education is an important part of the pedagogy and so is the place for the tuition.